PERGULATAN POLITIK KUASA DI BALIK TERBENTUKNYA CALON KEPALA DAERAH DALAM PEMILIHAN KEPALA DAERAH KABUPATEN GIANYAR ERA REFORMASI - Artayasa, I Made; Anggreni, Ni Wayan (Universitas Wijaya Kusuma Surabaya, 2025)
The political power struggle in determining the candidate for regional head of Gianyar regency in the reform era requires a long process. Three times in the regional head elections in Gianyar regency, there was no permanent coalition in each period, and only two regional head candidate pairs could be determined for the 2008, 2012, 2018 and 2024 elections. This research uses qualitative methods with data collection techniques through observation, document collection, in-depth interviews, and online searches. This research found two coalitions, each led by PDIP and Golkar. PDIP collaborated with Puri Gianyar and the extended family of Warih Dewa Manggis Sakti and Golkar with Puri Ubud and the family of Dalem Sukawati. With two pairs of regional head candidates, the political temperature in the Gianyar district is quite warm and interesting. There was a fight between PDIP and the Golkar party, Gianyar castle and Ubud castle and a sibling fight between Agung Baratha and his younger brother Agung Gde Agung. Figures who receive recommendations to be appointed as regional head candidates cannot be separated from the various social capital they possess.